Comparison of Treatment Insomnia Disease Between Prescription Medication and Cognitive Behavioral Therapy Using Rstudio - Ibrahim, Siti Aqilah; Zuraidin Mohd Safar (Applied Information Technology And Computer Science, 2021)
Abstract: Text mining is an obscure data or procedure to accumulate data from the knowledge that we got. Text mining can combine information from numerous sources. This project focuses to extract the knowledge to seek out the amounts of occurrences for every term to work out the treatment of insomnia between prescription medication and cognitive behavioral therapy. There are two technique that has been use which is information extraction and classification. Information extraction is that the process of extracting specific (pre-specified) information from textual sources which is data from prescription medication and cognitive behavioral therapy. There are five algorithms that has been used which is Naive Bayes, PART, IBk, SGD and Random Forest. These five algorithms are wont to find the f-measure score. F-measure score determine the diseases whether can treat which prescription medication and cognitive behavioral therapy. Then, the results f-measure of every algorithm were compared to understand the acceptable treatment for insomnia disease. There are five phases during this research. First, before start a search we’d like to form a planning. The second is that the data collected from PubMed. After collect the info, subsequent phase is employed an information extraction. Then we categorized or classify the info. Lastly, we analyses the result that has been produce